Evaluating Carbon Footprint in the Life Cycle Design of Residential Concrete Structures in Jordan - Omar Al-Omari; Ahmad Alkhdor; M. Abed Al-Rawashdeh; M. R. Al-Ruwaishedi; S. B. Al-Rawashdeh (Salehan Institute of Higher Education, 2023)
The construction industry is a significant source of greenhouse gas emissions, and there is a growing global interest in reducing the environmental impact of carbon dioxide emissions associated with building construction and operation. Concrete, the most commonly used material in construction, is known to release a substantial amount of environmentally harmful waste throughout its life cycle, including production, construction, operation, and demolition. The worldwide production and consumption of concrete contribute to approximately 5% of all human-related CO2 emissions each year. To assess the carbon footprint of concrete manufacturing and its application in construction projects, a comprehensive approach called life cycle assessment (LCA) is necessary. This paper presents a new process-based LCA approach to analyze carbon emissions and evaluate the carbon footprint of concrete from raw material extraction to the end-of-life stage. To address carbon emissions throughout the life cycle of concrete structures in the Middle East, the study adopts a case study approach, focusing on selected concrete structures in Jordan. The findings from these case studies highlight that the operational phase of concrete structures is the primary contributor to carbon emissions. By thoroughly examining the carbon cycle within structures and their interactions with the surrounding ecosystem, significant reductions in CO2 emissions, environmental deterioration, and its consequences can be achieved.Â Doi: 10.28991/CEJ-2023-09-07-07 Full Text: PDF